The value of stilbestrol in beef cattle rations, wintering phase. - Richardson, D.; Baker, F.H.; Good, D.L.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Forty Hereford steer calves averaging about 450 pounds were divided as equally as possible into four lots of 10 animals each. Two lots served as controls and the other two lots received 10 mg. of stilbestrol per head daily in the soybean meal. Ten Hereford heifer calves averaging about 335 pounds were divided as equally as possible into two lots of five animals each. One served as control and the other received 10 mg. of stilbestrol per head daily in the soybean meal. Atlas sorghum silage was used as the roughage in all lots and the animals received all they would clean up each day. The concentrate part of the ration consisted of 1 pound of soybean meal and 4 pounds of ground milo grain for all lots. A mineral mixture of 2 parts steamed bone meal and 1 part salt and salt were fed free choice. Water was available at all times. Eleven yearling Hereford steers were used in the digestion study. The ration used was chopped alfalfa hay and cracked milo grain fed at, a ratio of 1 part hay to 3 parts grain. The study was made with all steers and then repeated with stilbestrol. Thus, each animal served as his own control. The stilbestrol was fed at the rate of 10 mg. per head daily. The steers were fed in stanchions, and canvas collection bags. were used to collect the feces for chemical analyses.
Keywords: Beef; Stilbestrol; Digestibility; Gain